MODERN METHODS OF INCREASING PHYSICAL PREPAREDNESS INDICATORS AND TRAINING CADETS AND STUDENTS FOR EXTREME SITUATIONS (Web of Teachers: Inderscience Research, 2025)
This article scientifically analyzes modern methods for enhancing the physical preparedness of cadets and trainees and preparing them for effective action in extreme situations. The research highlights the significance of interactive sessions, innovative technologies, virtual training, exercises that develop stress resilience, and psychophysiological preparation. The results of conducted experiments demonstrate that modern approaches improve physical indicators by 15-25%, increase stress resistance, and optimize speed of action in extreme situations. The article provides scientific and practical recommendations for implementing advanced technologies in the process of training cadets and trainees.